Costume - Amano, Tatiane Kaori [UNESP] (2017)
dress in a video performance, which represents the normotic concepts present in our daily lifes. In this way, I seek to characterize this final project by developing a paper garment, which is a fragile and ephemeral material, conceptualizing the various harmful habits present in our life, called normose.